Systematization of the evaluation model of vocabulary control in repositories: research report with the Unesp Institutional Repository - Fujita, Mariangela Spotti Lopes [UNESP] (Univ Estadual Campinas - Sistema Bibliotecas, 2022)
Introduction: Vocabulary control in information resource storage, treatment and retrieval systems is necessary to obtain consistency between indexing and retrieval in order to avoid informational dispersion. Digital repositories in universities are currently fundamental in the organization and management of knowledge generated by scientific, technological, artistic, and administrative production, however, it is necessary to verify the availability of controlled vocabulary and how vocabulary control is carried out. Objective: With the objective of systematizing a proposal for vocabulary control and the use of controlled vocabularies in university repositories managed by libraries, an evaluation model was developed that proposes to systematize methods, procedures, resources, and techniques. Methodology: For this, the development of the investigation carried out exploratory research with bibliographic and documentary research and applied research in the Unesp Repository. Results: The results obtained constituted an Action Plan, discussed and elaborated by the Study Group, composed of six actions and nine studies to evaluate and control vocabulary in university repositories about: vocabulary control in indexing by professionals and non-professionals; vocabulary control in retrieval; use of subject metadata from academic papers; keyword matching; analysis of terminological variations at semantic, syntactic and pragmatic levels; analysis of transaction logs for searches by subject. Conclusion: It is concluded that the systematization of actions in an evaluation model is relevant for university repositories to incorporate the advances offered by vocabulary control in their routines and, mainly, for the contribution of new terms arising from scientific and technological evolution.
Keywords: Vocabulary control; Documentary languages; Institutional repositories; Evaluation